Experimental Study on the Strength Characteristics of Expansive Soils Improved by the MICP Method. (25th March 2022) - Tian, Xuwen; Xiao, Hongbin; Li, Zixiang; Li, Zhenyu; Su, Huanyu; Ouyang, Qianwen
Abstract : Microbially induced calcite precipitation (MICP) has been a promising method to improve geotechnical engineering properties; however, there are few literatures about the application of the MICP method to improve the strength characteristics of expansive soils with low permeability. In this paper, a series of CD triaxial tests were carried out to investigate the effect of the MICP method on the strength characteristics of the expansive soils. The results show that the shear strength of the specimens increased with the increase in the cementation solution and eventually reached a stable value. The MICP method can significantly improve the shear strength index of the expansive soils. The cohesion of the expansive soils was increased from 29.52 kPa to 39.41 kPa, and the internal friction angle was increased from 20.13° to 29.58°. The stress-strain curves of expansive soil samples improved by the MICP method show a hyperbolic relationship, which is characterized by strain hardening. The hyperbolic model was chosen to describe the stress-strain relationship of the expansive soils improved by the MICP method, and the predicted results were in good agreement with the measured results. Moreover, we performed a scanning electron microscope (SEM) experiment and revealed the mechanism of the MICP method to improve the strength characteristics of expansive soils. The conclusions above can provide a theoretical basis to further study the strength characteristics of improved expansive soils by the MICP method.